TAKSONOMI TRANSENDEN (PARADIGMA BARU TUJUAN PENDIDIKAN AGAMA ISLAM) - Heriadi, Heriadi (Jurnal Cakrawala Ilmiah, 2025)
The Taxonomy of the Objectives of Islamic Education in the Qur'anic Perspective. This study is initiated from a thought that "the objective of Islamic education is to make students good". The word "good" becomes the key as well as the entrance to formulate the objective of Islamic education in this study, namely by examining the concept of "good" in the Qur’an. The concept studied by using a model of thematic tafsir (mawdhu’iy) approach. With this approach the word "good" was sought through three stems, i.e., the words ahsana-yuhsinu, saluha-yasluhu and khairun with their various shapes and changes in al-Qur’an. Then the classification arranged using the theory of taxonomy. The focus of this research conducted is: How is the taxonomy of the objectives of Islamic education in the Qur’an perspective. The finding this research of the objectives of Islamic education taxonomy is called the Trancendent Taxonomy. Namely the classification of the objectives of Islamic education which is divided into three dimensions based on the Holy Qur’an, these are ilahiyyah (divinity), insaniyyah (humanity) and kauniyyah (naturality) dimensions.